2015
DOI: 10.1017/jns.2014.70
|View full text |Cite
|
Sign up to set email alerts
|

Hypocholesterolaemic effect of rat-administered oral doses of the isolated 7S globulins from cowpeas and adzuki beans

Abstract: The role of seed proteins, especially soyabean 7S globulins, in controlling dyslipidaemia is widely acknowledged. Amino acid sequence homology among the proteins of this family could reflect similar biological functions in other species. The aim of the present study was to unveil a hypolipidaemic effect of the 7S globulins from cowpeas (7S-C) and adzuki beans (7S-A), administered orally to rats fed a hypercholesterolaemic (HC; high cholesterol and TAG) diet for 28 d. A total of forty-five rats were divided int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
35
2
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(45 citation statements)
references
References 57 publications
6
35
2
1
Order By: Relevance
“…Also, according to Pincus and Schaffner (1996), AST and ALT are released markedly into serum as a result of severe hepato-cellular injury. Ferreira et al (2015) reported similar results for the ALT activity in the hypercholesterolemic rats. The increase in the ALT activity continued and became significant in case of the HFHC group which was treated with rosuvastatin (48.00 ± 2.11 U/L) compared to the negative control group (30.33 ± 2.39 U/L) indicating a negative effect of rosuvastatin on the liver.…”
Section: Resultssupporting
confidence: 68%
“…Also, according to Pincus and Schaffner (1996), AST and ALT are released markedly into serum as a result of severe hepato-cellular injury. Ferreira et al (2015) reported similar results for the ALT activity in the hypercholesterolemic rats. The increase in the ALT activity continued and became significant in case of the HFHC group which was treated with rosuvastatin (48.00 ± 2.11 U/L) compared to the negative control group (30.33 ± 2.39 U/L) indicating a negative effect of rosuvastatin on the liver.…”
Section: Resultssupporting
confidence: 68%
“…Finally, the 7S globulins component of dietary pulses may decrease LDL‐C. The 7S globulins are a family of proteins commonly found in legumes that have been shown to be involved in the cholesterol‐lowering effects of various legumes, including soybeans and dietary pulses, in cell culture and animal studies. The exact mechanism by which this protein lowers cholesterol, however, is currently unclear …”
Section: Systematic Reviews and Meta‐analyses Of Randomized Controllementioning
confidence: 99%
“…Some epidemiological studies have strongly indicated that legume consumption reduces the risk of coronary heart diseases (Bazzano, Thompson, Tees, Nguyen, & Winham, ; Ha et al., ). From previous studies, hypocholesterolemic ability of 7s globulin from cowpeas, cowpea protein isolates, and cowpea seeds was well documented (Ferreira et al., ; Frota, dos Santos Filho, Ribeiro, & Arêas, ; Frota, Mendonça, Saldiva, Cruz, & Arêas, ). From our previous study, we observed that raw cowpea‐incorporated experimental diets modulated serum lipids and serum antioxidant activity in Wistar rats (Perera et al., ; Weththasinghe, Liyanage, Vidanarachchi, Perera, & Jayawardana, ).…”
Section: Introductionmentioning
confidence: 92%